Development of Sports Human Resources to Improve Com-petence in Adios UTP Athletics Organization - Bagus Kuncoro; Ronny Suryo Narbito; Novendika Singgih P; Umar Syahid; Baskoro Baskoro (LITERACY : International Scientific Journals of Social, Education, Humanities, 2026)
This study aims to analyze the effect of HR development on improving the competencies of sports human resources within the ADIOS athletic club at Universitas Tunas Pembangunan (UTP) Surakarta. A quantitative approach was employed using a descriptive-verificative survey method. The research population consisted of all members of the ADIOS UTP club, including coaches, administrators, and active athletes, with total sampling used as the sampling technique. The research instrument was a Likert-scale questionnaire that had been tested for validity and reliability. Data were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) through the SmartPLS software. The results revealed that HR development comprising training, mentoring, performance evaluation, and organizational empowerment has a positive and significant effect on enhancing sports HR competencies, including technical knowledge, managerial skills, and professional attitudes. A path coefficient value of 0.820 and an R² value of 0.672 indicate a substantial relationship between variables. This study concludes that a structured HR development strategy can serve as a key determinant in shaping highly competent sports human resources. These findings are expected to serve as a reference for sports organizations in higher education institutions in designing performance development systems focused on sustainable HR capacity building.